The role of e-government in enhancing the institutional performance - مصطفى الملا عبد الرحمن; نوح مها طالب (Journal of Economics and Administrative Sciences, 2018)
Abstract The research aims to study the role of e-government in enhancing institutional performance. The dimensions of e-government are: (support and commitment of senior management, technical structures, organization and human resources, knowledge and information, work procedures, attention to citizens’ satisfaction, and client parties),while the dimensions of institutional performance are: (Service improvement, innovation, efficiency and effectiveness). The research used electronic questionnaire as a main tool for data collection, The questionnaire included all the employees in the e-government project in Department of Government Coordinate and Citizen Affairs at the General Secretariat of the Council of Ministers in all its administrative level and branches whom number are (169)and the response rate was (100%), a number of statistical methods were used to process the data. The research assumed that e-government is related to institutional performance and at the same time affects it, a set of conclusion has been reached, but the most important is that reflecting the usefulness of e-government on the efficiency of work and its procedures and thus the quality of service provided to the citizen by reducing effort, tim and cost. the development of the project is measured by knowing the citizen’s satisfaction with the services provided. All of the above, we conclude that the use of the e-government technique in all aspects of the institutional work has a significant impact on improving the institutional performance to achieve its excellence, which is also reflected positively on the performance of the parties dealing with the institution. The research recommended a set of recommendations, the most important of which is the application of this technique in all Institutions of the Iraqi state, and encourage research related to this area for its success and spread.